DECONSTRUCTING EMPOWERMENT OF PEOPLE WITH DISABILITIES AT GIANYAR SENANG HATI FOUNDATION, BALI - Wahyuni, Anak Agung Nyoman Sri; Wirawan, AA Bagus; Kumbara, Anak Agung Ngurah Anom (E-Journal of Cultural Studies; Volume 10, Number 2, May 2017, 2017)
Globalization extraordinarily affects the Senang Hati Foundation. The roles played by the agents of empowerment such as the Non-government OrganizationS and government are enormous. The government should pay attention to every citizen, including those with disabilities as they also need justness, as stated in the Five Principles ‘Pancasila’ and the 1945 Constitution and the Act Number 4 of 1997 concerning people with disabilities, which was then changed into the Act of the Republic of Indonesia Number 8 of 2016 concerning people with disabilities. This present study is intended to identify the empowerment of the people with disabilities at the Gianyar Senang Hati Foundation, Bali. The qualitative method is used. The data were taken from the primary data source and secondary data source. The data were obtained through observation, in-depth interview, and library research. The theory of hegemony, the theory of deconstruction, and the theory of social practice are used in the present study. The result of the study shows as follows. First, the Foundation has four programs which are implemented to empower people with disabilities. They are social program, educational program, health program, and economic program. Second, the obstacles the Foundation faces can be divided into two. They are the internal obstacle and external obstacle. Third, the obstacle affects the existence of the Foundation, its management, its members, the government, donators and society. The finding of the study is that the Foundation has not been able to empower all of its members yet. In addition, the agents of the empowerment of people with disabilities have different interests.